Clinically manifested major health problems of crossbred dairy herds in Urban and Periurban production systems in the central highlands of Ethiopia - Lema, M.; Kassa, T.; Tegegne, Azage (Springer, 2001)
The major clinical diseases of crossbred dairy herds were investigated for two years in a milk shed in Addis Ababa. Animals in 38 herds were randomly selected and visited weekly. Diagnosis of diseases and causes of death were based on clinical observation. Disease conditions were categorized into 8 groups, the mean annual incidence for all diseases being 44.7 percent. Reproductive diseases and clinical mastitis were most frequently observed, whereas gastrointestinal disorders, respiratory tract diseases, locomotor disorders and metabolic diseases each occurred in less than 5 percent of the cattle. Specific infectious and miscellaneous disease conditions each had annual incidence of about 6 percent. Cows and young stock were most affected and diseases were more frequent in urban situations than in periurban situations. Herd size and season significantly influenced the incidence of disease but study year did not. The crude mortality rate was 4.2 percent.